# Answer to Question #10812 in Algebra for Melvin Henriksen

Question #10812

Please factorize the polynomial (x+y)^2+3xy^2-x^3+xy-y^3+3x^2y

Expert's answer

If we take g1=x+y and g2=xy then our expression can be simplified as

(g1)^3+3(g1)(g2)+g2-(g1)^3+3(g1)(g2)=(6g1+1)g2=

=(6x+6y+1)xy

(g1)^3+3(g1)(g2)+g2-(g1)^3+3(g1)(g2)=(6g1+1)g2=

=(6x+6y+1)xy

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment